2017
DOI: 10.1097/md.0000000000006454
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation during cardiopulmonary bypass for prevention of respiratory insufficiency

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 29 publications
(31 reference statements)
1
34
0
1
Order By: Relevance
“…In contrast, a small study of fifty‐nine patients prospectively randomized to continuous ventilation and no ventilation, during CABG on CPB, showed there was no statistically significant difference in most of the inflammatory makers (IL‐6, IL8, IL‐10, and lactate) . A recent meta‐analysis for patients undergoing cardiac surgery and received ventilation during CPB included seventeen trials with 1162 patients, showed that ventilation during CPB significantly increased post‐CPB PaO 2 /FiO 2 ratio, but there was no sufficient evidence to show that ventilation during CPB could influence long‐term prognosis of these patients …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a small study of fifty‐nine patients prospectively randomized to continuous ventilation and no ventilation, during CABG on CPB, showed there was no statistically significant difference in most of the inflammatory makers (IL‐6, IL8, IL‐10, and lactate) . A recent meta‐analysis for patients undergoing cardiac surgery and received ventilation during CPB included seventeen trials with 1162 patients, showed that ventilation during CPB significantly increased post‐CPB PaO 2 /FiO 2 ratio, but there was no sufficient evidence to show that ventilation during CPB could influence long‐term prognosis of these patients …”
Section: Discussionmentioning
confidence: 99%
“…Thirty-five (n = 35) articles were excluded due to no CPB surgery or intraoperative ventilation was discussed (n = 27), case reports (n = 2), protocol design (n = 2), trials involving cardiac surgeries in children (n = 1), thesis (n = 1), and no full-text available (n = 2). Therefore, 13 articles were included for further description in our qualitative analysis: systematic review and meta-analysis (n = 1) [2] , meta-analysis (n = 1) [8] , randomized clinical trials or RCTs (n = 3) [9][10][11] , prospective observational (n = 1) [12] , and reviews (n = 7) [4][5][6][13][14][15][16] . Figure 1 describes the flow diagram corresponding to our search.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the ratio between the arterial oxygen partial pressure (PaO 2 ) and the inspired fraction of oxygen (FiO 2 ) or PaO 2 /FiO 2 ratio was reported in the only prospective observational study [12] . Likewise, one meta-analysis by Chi et al [8] included 17 trials and 1,162 patients undergoing cardiac surgery evaluating the oxygenation index (PaO 2 /FiO 2 ratio) and the alveolar to arterial oxygen difference (AaDO 2 ) after CPB. Rate of PPCs, shunt fraction, hospital LOS, and postoperative AaDO 2 (4 h after CPB) were also estimated.…”
Section: During Cpb and Perioperative Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, numerous studies have sought to compare ventilation during CPB to identify an optimal strategy. Recent systemic reviews have examined, variously, CPAP versus conventional treatment (ie, no ventilation while on bypass 7 and, more broadly, "ventilation" versus "no ventilation" during CPB) 8 and have elicited similar findings-that some form of ventilation or delivery of CPAP during CPB appears to be better than none with regard to measured oxygenation parameters. These studies also have not been able to identify a significant difference in clinical outcomes such as postoperative respiratory morbidity or length of stay.…”
mentioning
confidence: 99%